Diamondback Moth Management in Cole Crops - Purity K. Muthomi; Dakshina Seal; Oscar E. Liburd (EDIS)
The diamondback moth, Plutella xylostella (Linnaeus), is a significant pest of cole crops such as cabbage, Chinese cabbage, broccoli, Brussels sprouts, collards, kale, kohlrabi, mustard, radish, carinata, turnips, and watercress. Globally, the annual cost of managing the DBM is estimated to be USD 4 to 5 billion. The pest originated in Europe but is now widely distributed wherever cole crops are extensively grown. DBM has become widespread due to its high dispersal ability, multiple generations per year, and potential to develop resistance to most commonly used insecticides. DBM management is heavily reliant on chemical control, but DBM is notorious for developing resistance to many classes of insecticides, so frequent pesticide applications can lead to insecticide resistance, ineffective pest suppression, and yield losses. Therefore, to manage DBM, a good integrated pest management (IPM) strategy is critical.